Plastic shrinkage cracking and bleeding of concrete prepared with alkali activated cement - Faris Matalkah; Yaser Jaradat; Parviz Soroushian (Heliyon, 2019)
Restrained shrinkage cracking that appears on concrete surfaces during construction, or while concrete in the curing process adversely affect the long-term durability and other performance attributes of concrete-based-infrastructures. This study investigates the effects of early-age surface cracking on restrained shrinkage concrete made of alkali activated cement. Concrete produced using this class of cement differs from ordinary Portland cement concrete in terms of surface qualities and some other properties. Bleeding which could be a main cause of plastic shrinkage cracking was measured and compared with that of Portland cement. Rheological tests were performed to gain further insight into factors that may influence the early-age performance of the cement paste. Portland cement was used as control for comparative assessment of the alkali activated cement performance. Experimental test showed that alkali activated cement improved the characteristics of the newly produced concrete. The concrete prepared using alkali activated cement has low tendency to bleeding and higher resistance to plastic shrinkage, also, the viscosity and yield stress of the alkali activated cement paste were relatively higher when compared to those of ordinary Portland cement paste. Test data collected from rheological and bleeding tests on the alkali activated cement concrete were used to explain its desired resistance to plastic shrinkage cracking.